Natural-born proud : a revery - Martin, S. R. (Sennie Rudolph), 1935- (Book collections on Project MUSE., 2010)
A young man from Monterey and his younger brother go on their first deer hunt with their minister father and his friends. The setting is 1950s northern California, in country where, from the right height, one can see Mt. Shasta in one direction, Mt. Lassen in the other. It is a region of small, insular towns, and although it is a familiar hunting ground for the Reverend and his buddies, not everyone there welcomes black hunters. Father and son both shoulder their pride, and a racial confrontation seems inevitable. Among the lessons young Satch learns is the sometime advantage of wit and spine. During their days in the wilderness, the brothers are initiated to the right practice of the hunt and camp and to the ribald talk, needling banter, camp tales, and occasional aggravation of sundry friends. Hunting has a primal nature, but as Satch sees, so may the variable interactions of men.